HEALING THROUGH CELEBRATION: A Short Survey of Select Christian Sacramental Celebrations - Kochappilly, Paulachan (Journal of Dharma, 1999)
Religions guide believers to wholeness, holiness and salvation within the purview of their lived and living traditions. It is through religious celebrations that a religion generally manifests its principles and way of life. In order to promote life and the celebration of it, religion advocates and stipulates certain means and methods, which in most cases, come to the limelight through religious celebrations, for there is an epiphany of the ethos of the community taking place in every celebration